1995
DOI: 10.1111/j.1476-5381.1995.tb16346.x
|View full text |Cite|
|
Sign up to set email alerts
|

Improved survival and reversal of endothelial dysfunction by the 21‐aminosteroid, U‐74389G in splanchnic ischaemia‐reperfusion injury in the rat

Abstract: Anaesthetized rats subjected to total occlusion of the superior mesenteric artery and the coeliac trunk for 45 min developed a severe shock state (splanchnic artery occlusion, SAO shock) resulting in death within 70-90 min after release of the occlusion. Sham-operated animals were used as controls. 2 Survival rate, survival time, serum tumour necrosis factor (TNF-z), white blood cell (WBC) count, mean arterial blood pressure (MAP), plasma malonylaldehyde (MAL), myeloperoxidase activity (MPO) and the responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 24 publications
1
15
0
5
Order By: Relevance
“…In this study, we observed that EPC-K1 reduced morphologic changes in renal tissue and mitochondria after renal I/R. We also observed a reduction in the kidney levels of MDA, which is produced when lipids are damaged by ROS and used as an indicator of ROS activity in I/R injury [27]. Furthermore, EPC-K1 significantly suppressed ROS activity in a murine macrophage-like cell line.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we observed that EPC-K1 reduced morphologic changes in renal tissue and mitochondria after renal I/R. We also observed a reduction in the kidney levels of MDA, which is produced when lipids are damaged by ROS and used as an indicator of ROS activity in I/R injury [27]. Furthermore, EPC-K1 significantly suppressed ROS activity in a murine macrophage-like cell line.…”
Section: Discussionmentioning
confidence: 74%
“…Oxygen free radicals, in particular the superoxide radical [16], and tumor necrosis factor-␣ (TNF) [17] have been incriminated in this abnormal vasoconstrictive response which may involve an inhibitory effect on nitric oxide (NO). 21-AS, including U74389G, have been shown to inhibit superoxide radical production [18] and to lower TNF levels [19]. U74006F, like superoxide dismutase, was found to restore in vitro endothelium-dependent relaxation of superior mesenteric artery rings in endotoxin-shocked rats [20].…”
Section: Discussionmentioning
confidence: 98%
“…Upon reaction, hydroxyl radicals themselves instantly disappear, but the reaction damages biomolecules, as well as cell and tissue functions. Malondialdehyde (MDA) is produced when lipids are damaged by ROS [21] and is thus a useful indicator of ROS activity in ischemia-reperfusion injuries [22]. Cepharanthine administration was associated with improvement of ischemia-reperfusion-induced changes in mitochondrial morphology and tissue MDA levels, suggesting that cepharanthine's protective effects may be mediated at least in part by ROS inhibition.…”
Section: Discussionmentioning
confidence: 99%